Cell biology analogies in Brazilian biology textbooks : a teaching guide based on FAR model - Oliveira, Iago Taveira (2019)
From a well-established model for the use of analogies in science teaching (Focus, Action, Reflection – FAR Guide) this research aimed to develop a teacher support resource (teacher guide) based on the four most frequent cell analogies in Brazilian biology textbooks which were: DNA as a spiral staircase, complex substrate enzyme as a key and lock, ATP as currency and mitochondria as a power plant. This teacher guide was evaluated by pre-service biology teachers from a Brazilian public university. Perceptions and recommendations were collected by questionnaires, participant speeches’ recording and a field notebook. Students’ responses were tabulated and analyzed, and these results were evaluated for a current version of the teacher guide. The comprehension of the content was perceptible by the majority of participants, however some of them showed doubts about analogies’ limits. FAR Guide was considered a good way to plan use of analogies to a cell biology class and a viable didactic resource to be used in the Brazilian educational context.